Assessing skill capability of artisans and craftsmen in Nsukka industrial market, Enugu State, Nigeria - Isife Raphael Lebechukwu; Akpen-Ade Peter (Ianna Journal of Interdisciplinary Studies, 2021)
Background: Most tradesmen are trained through traditional apprenticeship system, hence ranked lowest in the labour market. Although, Nigerian artisans contribute significantly to skill acquisition and economic development, their poor training background seem to make them deficient to cope with current technological innovations and practices. For any teaching to be impactful, suitable training needs has to be standard; the survival strategies for entrepreneurship in a declining economy can be vested in training artisans, tradesmen and entrepreneurs who will man the small and medium enterprises for better economy.